The Efficacy of Schema Therapy on Rumination, Depression, and Personality Function of Women with Bulimia Nervosa - Farzin Bagheri Sheykhangafshe; Fereshteh Rezazadeh Khalkhali; Vahid Savabi Niri; Maryam Zolfagharnia; Nahid Mikelani (پژوهش‌های کاربردی روانشناختی, 2024)
The present study was conducted to investigate the effectiveness of schema therapy on rumination, depression, and personality function of women with bulimia nervosa. The semi-experimental research method was pre-test-post-test with a control group. The statistical population of this study consisted of women in Tehran who were diagnosed with bulimia nervosa in 2023. 30 women were randomly assigned to the experimental and control groups in accordance with the research's inclusion criteria. Rumination (RQ), Beck depression (BDI), and personality function (PFQ) questionnaires were implemented to evaluate the groups. Following ten 90-minute schema therapy sessions for the experimental group, the participants responded to the research questionnaire again. Finally, the data were subjected to multivariate analysis of covariance using SPSS-24. Schema therapy significantly decreased rumination (F=23.51), depression (F=50.04), and increased intimacy (F=47.16), empathy (F=41.83), and self-direction (F=30/04) and identity (F=32/77) in women with bulimia nervosa (P<0.01). The results indicate that schema therapy has reduced psychological disorders and enhanced the personality function of women with bulimia nervosa. Measures should be implemented to identify and treat vulnerable populations in light of the significant changes in people's lifestyles that the COVID-19 pandemic has induced.